Integrating habitat connectivity and fishing pressure to promote migratory marine species conservation - Guodong Li; Cuicui Feng; Haibin Han; Xinyun Ge; Rongliang Zhang; Fangping Cheng; Xin Fang; Han Dong; Chang Liu; Wei Huang; Jiangning Zeng (Reviews in Fish Biology and Fisheries, 2026)

Functional connectivity in China’s coastal MPAs: modeling critical corridors and restoration zones for economic fish under climate change - Han Dong; Xin Fang; Guodong Li; Fangping Cheng; Jiangning Zeng; Wei Huang (Frontiers in Marine Science, 2026)
Climate change is reshaping the distributions of marine species and disrupting functional connectivity among protected areas, yet few studies have quantified how these shifts alter the performance of marine protected area (MPA) networks. This study assessed climate-driven changes in functional connectivity for eight economically important fish species across 193 coastal MPAs in China under current conditions and two end-of-century scenarios (SSP1-2.6 and SSP5-8.5, 2090–2100). Ensemble species distribution models (mean AUC: 0.91–0.98; mean TSS: 0.75–0.93) were used to project h\abitat suitability, which was converted into resistance surfaces and analyzed via least-cost path and circuit-theory modelling to identify inter-MPA corridors, pinch-points, and barrier zones. Habitat responses diverged sharply between thermal guilds: warm-water species expanded in total area ( B. taipingensis : +434.6% under SSP5-8.5), whereas cold-temperate species contracted severely ( L. polyactis : −57.8%, with complete loss of high-suitability habitat). Functional connectivity exhibited asymmetric changes at the network level. Effective resistance declined 99% for A. japonica but increased 29-fold for S. niphonius under SSP5-8.5. Critically, corridor quantity and quality diverged for B. taipingensis , which gained 93% more corridors yet experienced a 47.8% increase in effective resistance—demonstrating that network expansion does not ensure improved connectivity. pinch-point counts increased across all four sea regions under SSP5-8.5 (most markedly in the Beibu Gulf: 16 to 28), and dual-stress zones where bottlenecks coincided with high-restoration-potential barriers concentrated along the Zhejiang–Fujian coast, the Bohai Strait, and the Pearl River Estuary. These results demonstrate that static MPA networks are progressively misaligned with dynamic species connectivity requirements, and identify spatially explicit priority zones where adaptive management intervention would yield compounding benefits for network-wide resilience.

Combined effects of climate and anthropogenic change on habitat suitability and distribution of threatened marine species in China’s coastal waters - Han Dong; Guodong Li; Xin Fang; Fangping Cheng; Jiangning Zeng; Wei Huang (Frontiers in Marine Science, 2026)
Understanding how climate change and anthropogenic stressors jointly affect threatened marine species is critical for conservation planning, yet integrated assessments remain scarce in China’s coastal waters. Using an ensemble species distribution modelling framework (Biomod2) with six algorithms, we projected habitat suitability for ten threatened marine species under climate-only and global-change scenarios for 2040–2050 under SSP1-2.6 and SSP5-8.5. Predictors included 13 natural variables and four anthropogenic variables (fishing pressure, coastal pollution, aquaculture intensity, and shipping density). Ensemble models achieved high predictive performance under both predictor sets (climate-only: mean TSS = 0.87, AUC = 0.96; global-change: TSS = 0.80, AUC = 0.92), consistently outperforming individual algorithms. Mean sea temperature, dissolved oxygen, and bathymetry were the dominant natural drivers, while fishing pressure (up to 16.2%) and coastal pollution (up to 29.5%) were the most influential anthropogenic factors. Under climate-only scenarios, species distribution centroids shifted northward at mean rates of 22.12 km·decade -1 (SSP1-2.6) and 47.91 km·decade -1 (SSP5-8.5), with Tachypleus tridentatus (98.99 km·decade -1 under SSP5-8.5) and Hippocampus trimaculatus (83.64 km·decade -1 ) showing the greatest displacement. Habitat responses were highly species-specific: A. glauca , M. griseus , and H. trimaculatus exhibited net expansion, whereas C. mydas and P. largha experienced consistent contraction. Critically, incorporating anthropogenic stressors substantially reduced habitat availability across the assemblage, with mean suitable area per species declining from 31, 813 km² (climate-only) to 19, 080 km² (global-change), a 40.0% reduction. Anthropogenic pressures even reversed climate-driven gains for several species, most notably H. nehereus (from +87.2% to −16.3% under SSP5-8.5) and S. kobiensis (from +2.1% to −86.0%), and intensified contractions for C. mydas and P. largha . Cumulative habitat suitability mapping further identified the Pearl River Estuary, western Taiwan coast, Yangtze River Delta, and central Bohai Sea as priority regions where climate refugia overlap with intense human activities. These findings demonstrate that anthropogenic pressures can transform potential climate refugia into ecological traps, amplifying climate-driven habitat loss, and underscore the urgent need for integrated marine spatial planning addressing both climatic and anthropogenic threats in China’s coastal waters.

Designing ecologically connected marine protected area networks under global change: the Yellow and Bohai Seas, China - Han Dong; Xin Fang; Guodong Li; Fangping Cheng; Jiangning Zeng; Wei Huang (Frontiers in Marine Science, 2026)
Accelerating climate change and chronic anthropogenic pressures demand connectivity-based design of marine protected area networks (MPANs). Yet integrating dynamic species responses and cumulative human pressures into spatial planning remains a key challenge, particularly in marginal seas at the land–ocean interface. As a biodiversity hotspot under intensive development, the Yellow and Bohai Seas (YBS) exemplify this complexity, yet how global change will reshape connectivity here remains unclear. Using ensemble species distribution models, we projected suitable habitats for 70 representative marine taxa under present-day conditions and two future scenarios (SSP1-2.6 and SSP5-8.5, representing low- and high-emission Shared Socioeconomic Pathways), generating multi-species natural resistance surfaces. These were combined with an entropy-weighted anthropogenic resistance layer—comprising fishing, shipping, mariculture, and pollution—to produce integrated resistance surfaces (IRS) for each scenario. Circuit theory was then applied to quantify ecological corridors, current density, pinch points, and barriers among 61 MPAs. Our results showed that: (1) climate forcing drove pronounced habitat redistribution, with cold-adapted taxa contracting within the Bohai Sea while warm-adapted species shifted poleward, especially under SSP5-8.5; (2) the IRS intensified overall (mean rising from 1.00 to 1.22), especially in the central-northern Bohai, while the southern Yellow Sea—particularly the central trough influenced by the Yellow Sea Cold Water Mass (YSCWM)—retained relatively low resistance, indicating a potential climatological corridor; (3) although total corridor length increased modestly (6,937 to 7,634 km), functional connectivity declined sharply, with Critical Corridors decreasing from 66 to 36 and effective resistance rising by 27%; (4) Grade-1 pinch points expanded by 35% and barrier clusters nearly tripled in area, concentrating where climate-degraded habitats overlap with intense human activities. Together, these drivers create a high-resistance Bohai core and more permeable Yellow Sea margins—a north–south divergence with direct consequences for species persistence and climate-driven range shifts. Embedding global change-adjusted corridor, pinch-point, and barrier metrics into spatial planning is therefore essential for maintaining MPA network resilience in the YBS and other marginal seas.

Deciphering structuring mechanism and increased health risk of antibiotic resistome from a coastal river basin to the downstream estuary and bay under anthropogenic disturbances - Xinyu Huang; Yuanzhen He; Lu Zhang; Jia Chen; Guoqing Zhang; Zhiguo Zhang; Wei Huang; Lukuo Ma; Fangping Cheng; Yuntao Wang; Xinyu Zhu; Feng Ju (Journal of Hazardous Materials, 2025)

The impact of summer Yangtze river runoff fluctuations on estuarine fronts dynamics and zooplankton communities from 2016 to 2023 - Yepeng Xu; Fangping Cheng; Xiao Ma; Ming Mao; Yuanli Zhu; Zhibing Jiang; Ziting Zheng; Jiangning Zeng; Lu Shou; Feng Zhou; Ping Du (Frontiers in Marine Science, 2025)
Estuarine fronts, which arise from the convergence of distinct water masses, exhibit considerable spatial and temporal variability and play a crucial role in shaping ecological dynamics within estuarine ecosystems. Despite their importance, due to limited data, there’s inefficiency understanding on how biological communities, particularly zooplankton, respond to these dynamic environmental features. The Yangtze River Estuary (YRE), a transitional zone between the Yangtze River and the East China Sea, is an ideal place in which to study the response of zooplankton communities to estuarine fronts, as freshwater discharge, offshore waters, and the Taiwan Warm Current converge here and form sediment and plume fronts in summer. We investigate zooplankton communities and environmental variables including temperature, salinity, turbidity, and Chlorophyll a (Chl a ) in the YRE during summer from 2016 to 2023, and examine the differences in spatial distribution of estuarine fronts and zooplankton community and the dominant environmental factors controlling zooplankton variation in different runoff years. Our findings found that the sediment fronts appeared around 122.5°E except in drought years (2022 and 2023); the plume fronts extended to 123.5°E and beyond during wet years (2016, 2020 and 2021), while shrank within 123°E in drought years. The zooplankton communities were classified into low-salinity, moderate-salinity, and high-salinity groups spatially in most years, but the low-salinity group had not been detected in the extreme drought year 2022. During flood years, low-salinity nearshore species such as Oithona brevicornis , Centropages dorsispinatus and Cladocera exhibited a notable increase in dominance, while the drought favored euryhaline species like Microsetella rosea . Furthermore, the turbidity, salinity and temperature all played significant roles in zooplankton spatial variation in wet years, while only salinity played as an important factor in drought years. These results implied the prominent sediment fronts and extended plume fronts in wet years shaped the zooplankton spatial variation collectively; in contrast, sediment fronts disappeared during drought years, and the plume fronts played a crucial role in shaping the zooplankton spatial variation. Besides, the extremely low runoff in 2022 has been shown to lead to obvious changes in zooplankton communities, which might affect fisheries stocks and require concern.

Characterization and risk assessment of microplastics in laver from the Yueqing Bay - Qikun Yang; Lukuo Ma; Kecheng Qiu; Zhihua Feng; Youji Wang; Zhen Zhong; Fangping Cheng; Tianqi Zhai; Jiangning Zeng; Wei Huang (Marine Environmental Research, 2024)

Vertical Fine-Scale Distribution of Calanus sinicus in the Yellow Sea Cold Water Mass During the Over-Summering Process - Jun Pan; Fangping Cheng; Fei Yu; Yongqiang Shi; Fan Sun; Guangcheng Si; Chuanjie Wei; Xinyuan Diao; Yongfang Zhao (Frontiers in Marine Science, 2021)
Calanus sinicus , a temperate copepod with a lethal temperature >27°C, is one of the key species in Chinese coastal marine ecosystems. The C. sinicus population increases in spring and declines in early summer annually due to increasing water temperature. Numerous C. sinicus individuals then congregate in the Yellow Sea Cold Water Mass (YSCWM) and remain under the thermocline from early summer to early autumn. Development and reproduction is halted in this cold and foodless bottom water and they avoid ascending to the hot surface water, which is regarded as an over-summering strategy. Based on discrete water sampling approaches, previous studies demonstrated that higher chlorophyll a (Chl a) levels appeared in the mixed hot surface water layer; however, the subsurface chlorophyll a maximum layer (SCML) has seldom been described. In the present study, various probes and a visual plankton recorder (VPR) were used to determine the fine vertical distributions of environmental factors and C. sinicus . VPR observations showed the ecological responses in fine scale and indicated that few C. sinicus individuals ascend at night, the main population preferred to remain below the SCML all day long. The results demonstrated that a constant thin SCML existed in the YSCWM area, and that the SCML location coincided with or was beneath the thermocline and halocline layers, where the temperature was suitable for C. sinicus . The relationship between abundance and Chl a, showed the diel vertical migration trend of C. sinicus to feed at night in the YSCWM area. In addition to temperature as a main influencing factor, dissolved oxygen concentrations and column depth were also influencing factors. Therefore, in addition to avoiding high surface temperature, energy supplement may be an important driving force confining the diel vertical migration of C. sinicus in the Yellow Sea in summer.

Creating novel chrysanthemum germplasm via interspecific hybridization and backcrossing - Xi Cheng; Sumei Chen; Fadi Chen; Yanming Deng; Weimin Fang; Fangping Tang; Zhaolei Liu; Wei Shao (Euphytica, 2011)